A method for preparing high-purity cupric oxide by using acid etching waste liquid
Patent Information
- Application Number
- CN202611310538.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-23
AI Technical Summary
①产品纯度不足
1.本发明通过“氧化吸附除杂-选择性pH沉淀-离子交换深度净化-反加缓冲碱液除氯-高温煅烧提纯”串联纯化工艺,采用过氧化氢预氧化将Fe2+转化为Fe3+,配合活性炭吸附去除有机杂质,再通过精确控制pH使Fe3+、Sn4+等杂质选择性沉淀,最后经离子交换树脂深度吸附残留微量金属离子,三重保障使铜净化液纯度大幅提升;最后经过反加混合碱液,将氯离子大幅度降低,经煅烧后最终氧化铜产品纯度可达98.2%以上,有效解决了现有化学沉淀法产品杂质含量高的技术难题。
Smart Images

Figure CN122957871A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic waste liquid recycling, and more specifically, to a method for preparing high-purity copper oxide using acidic etching waste liquid. Background Technology
[0002] Acid etching processes generate large quantities of copper-containing etching wastewater, with copper ion content as high as 5% to 15%, and also contain large amounts of chloride ions, free acid, and trace amounts of iron, tin, and other impurity ions. Direct discharge will cause serious heavy metal pollution and soil acidification, but the high concentration of copper resources in the wastewater makes it a "secondary mine" with great recycling value. Therefore, the efficient recovery of copper from acid etching wastewater and its conversion into high-value-added copper-based products has become a core issue for the green development and resource recycling of the PCB industry.
[0003] Currently, copper recovery technologies for acidic etching wastewater mainly include electrolysis, extraction-electrodeionization, and chemical precipitation. Membrane electrolysis separates the anode and cathode chambers using an ion-exchange membrane, depositing high-purity copper at the cathode while simultaneously recovering hydrochloric acid at the anode for etching solution regeneration, achieving copper recovery rates exceeding 99%. However, this technology requires highly corrosion-resistant equipment, involves significant initial investment, and can easily cause secondary pollution if the chlorine gas released at the anode is not properly controlled. Furthermore, issues such as scratches and breakage still exist during the copper foil stripping process. Extraction-electrodeionization offers good selectivity and high copper recovery rates, but extractant loss and organic phase entrainment increase operating costs, and residual copper ions in the raffinate often require further treatment. Chemical precipitation is one of the most widely researched and applied technical routes. Existing technologies include directly injecting acidic copper chloride etching wastewater into a 30%–35% sodium hydroxide solution to generate copper oxide, which, after washing, drying, and sintering, yields needle-like copper oxide with a purity greater than 99.0%. This method is relatively simple to operate, but the co-precipitation of copper ions with a large number of impurity ions is severe during direct alkaline precipitation, making it difficult to further improve product purity, and the problem of residual chloride ions is prominent. Another approach involves mixing acidic etching wastewater containing cuprous ions with an oxidant to oxidize the cuprous ions to copper ions, which are then directly reacted with an alkaline solution under conditions of pH ≥ 8 and temperature > 50℃ to form copper oxide. Although this method introduces an oxidation step, the subsequent step is still a direct precipitation, failing to effectively solve the problem of separating impurity ions from copper ions.
[0004] Current technologies for recovering acidic etching waste to prepare copper oxide still have the following prominent problems: ① Insufficient product purity. Existing chemical precipitation methods mostly involve one or two-step direct precipitation, where copper ions react with Fe... 3+ Sn 4+ Zn 2+ Ca 2+ Mg 2+The co-precipitation of impurity ions is severe, resulting in high impurity content in the product and making it difficult to consistently achieve a purity of over 98%. While some high-purity solutions can yield products with a purity of over 99%, the processes are complex and require demanding operational skills. ② High chloride ion residue. Acidic etching wastewater contains a large amount of chloride ions, and the residual chloride ion content in existing precipitation method products is generally high, which seriously affects the performance of copper oxide in electronic applications. Organic matter interference is severe.
[0005] ③ In addition to metal ions, acidic etching waste liquid also contains organic additives and photoresist residues from the etching process. If these organic substances are not effectively removed, they will be mixed into the product during precipitation, affecting the purity and activity of copper oxide. Existing technologies for treating organic substances mostly rely on simple activated carbon adsorption, lacking synergistic design with the oxidation step.
[0006] ④ The morphology of the product is difficult to control. The copper oxide precursors obtained by existing precipitation methods are mostly amorphous aggregates with wide particle size distribution and irregular morphology, which makes it difficult to meet the requirements of high-end applications for uniformity and dispersibility of copper oxide particles.
[0007] ⑤ The impurity removal process lacks a systematic approach. Existing technologies often involve single-step impurity removal processes, failing to form a complete purification chain from organic matter removal to selective metal ion separation and deep removal of trace impurities. There is a lack of synergistic effect between the various steps.
[0008] The technological development in the field of copper resource recycling is showing a trend of evolving from simple resource recycling to high-value and functional recycling. How to effectively remove organic matter, deeply remove various metal impurities, and control product morphology while simplifying the process, thereby improving the purity, specific surface area, activity and other electronic-grade performance indicators of copper oxide products, remains the focus and challenge of technological research. Summary of the Invention
[0009] The purpose of this invention is to provide a method for preparing high-purity copper oxide using acidic etching waste liquid. This method employs a series of purification processes: oxidation adsorption for impurity removal, selective pH precipitation, ion exchange for deep purification, reverse addition of buffer alkali for dechlorination, and high-temperature calcination for purification. This achieves efficient separation of copper ions from impurity ions such as iron, tin, zinc, calcium, and magnesium in the acidic etching waste liquid. After calcination, the final copper oxide product achieves a purity of over 98.2%, effectively solving the technical problem of high impurity content in copper oxide products produced by existing chemical precipitation methods.
[0010] The technical problem solved by this invention is achieved by the following technical solution.
[0011] On one hand, embodiments of this application provide a method for preparing high-purity copper oxide using acidic etching waste liquid, comprising the following steps: S1. After filtering the acidic etching waste liquid to remove suspended particles, heat it to 40-50℃ and stir to add hydrogen peroxide working solution; then raise the temperature to 50-60℃ and continue stirring to remove excess hydrogen peroxide; after cooling, add activated carbon and stir; filter to obtain purified copper-containing filtrate. S2. Heat and stir the purified copper-containing filtrate and adjust the pH, let it stand, filter to remove impurities, and obtain a copper-containing refined solution; S3. Add ion exchange resin to the copper-containing refined solution, stir, and filter to obtain a copper-containing purified solution; S4. Heat the copper-containing purification solution to 60-80℃, stir and add PEG. After dissolving, add basic copper carbonate seed crystals, stir, and then dropwise transfer to a sodium carbonate-sodium bicarbonate mixture. Continue stirring, and after standing, filter, wash, and dry, obtain basic copper carbonate powder. S5. High-purity copper oxide powder can be obtained by calcining, cooling and grinding basic copper carbonate powder.
[0012] Furthermore, in step S1, the hydrogen peroxide working solution has a mass fraction of 1% and is added slowly in batches at a stirring rate of not less than 300 r / min.
[0013] Furthermore, in step S2, the pH adjustment step includes first adjusting the pH of the filtrate to 1.0 with sodium hydroxide solution, and then slowly titrating with sodium carbonate solution to adjust the pH to 3.2-4.0, preferably 3.5.
[0014] Furthermore, in step S3, the ion exchange resin is a chelating cation exchange resin, and the addition amount is 10 g / L.
[0015] Furthermore, in step S4, the PEG is PEG-4000, and the addition amount is 2000ppm.
[0016] Furthermore, the amount of basic copper carbonate seed crystals added is 1%-3% of the total system mass.
[0017] Furthermore, the molar ratio of sodium carbonate to sodium bicarbonate is 1:30-50.
[0018] Furthermore, in step S5, the calcination conditions are calcination at 500℃ for 2 hours.
[0019] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects: 1. This invention employs a series of purification processes: "oxidative adsorption for impurity removal - selective pH precipitation - ion exchange for deep purification - reverse addition of buffer alkali for dechlorination - high-temperature calcination for purification," using hydrogen peroxide pre-oxidation to remove Fe. 2+ Converted to Fe 3+ In conjunction with activated carbon adsorption to remove organic impurities, and then through precise pH control, Fe... 3+Sn 4+ Impurities are selectively precipitated, and residual trace metal ions are deeply adsorbed by ion exchange resin. This triple protection significantly improves the purity of the copper purification solution. Finally, the chloride ion content is greatly reduced by adding mixed alkali solution. After calcination, the purity of the final copper oxide product can reach over 98.2%, effectively solving the technical problem of high impurity content in existing chemical precipitation products.
[0020] 2. This invention introduces PEG as a morphology regulator and dispersant during the precipitation and crystallization process of basic copper carbonate. Simultaneously, seed crystals are added to induce directional crystallization, effectively controlling the grain size and morphological uniformity of the precipitated product. This avoids the problems of severe agglomeration and wide particle size distribution found in traditional precipitation methods. The addition of PEG reduces the surface tension of the solution and improves the solid-liquid interface properties. The resulting basic copper carbonate precursor exhibits good dispersibility, and after calcination, the copper oxide particles are uniform in size and have controllable morphology, meeting the requirements of high-end applications.
[0021] 3. The method of this invention is simple in process and requires low equipment investment. It does not require the use of organic extractants or expensive membrane materials, and the main reagents are inexpensive and readily available. Meanwhile, the precipitate mother liquor (mainly composed of dilute NaCl solution) can be discharged in compliance with standards or reused in etching solution preparation after simple neutralization treatment, achieving high-value recovery of copper resources and effective removal of harmful components from the waste liquid. The calcination tail gas is CO2 and water vapor, with no secondary pollution, resulting in good environmental and economic benefits.
[0022] 4. The high-purity copper oxide product obtained by this invention has a purity ≥98.2%, chloride ion content ≤0.05%, and uniform particle size, which can meet the quality requirements for high-purity copper oxide in fields such as lithium-ion battery anode coatings, electronic ceramics, catalyst carriers, high-precision polishing fluids, and electroplating copper oxide powder raw materials, thus broadening the application space of the resource recovery product of acid etching waste liquid. Furthermore, according to the subsequent electroplating application requirements, the obtained copper oxide can also be used as an anode raw material to formulate high-purity electroplating solutions, realizing a complete resource recycling chain from waste liquid recovery to end-use applications. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a scanning electron microscope (SEM) image of the copper oxide obtained in Example 1 of the present invention; Figure 2 The graphs show the changes in purity and impurity content of copper oxide prepared in various embodiments and comparative examples of this invention. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0026] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to specific embodiments.
[0027] Example 1 This embodiment provides a detailed method for preparing high-purity copper oxide using acidic etching waste liquid, specifically including the following steps: S1. Take 1L of acidic copper chloride etching waste liquid, with a copper content of 125.2g / L, chloride ion concentration of 312.4g / L, acidity of 2.15N, and Fe content of 280ppm. After filtering with a precision filter bag to remove suspended particles, place it in a 2L beaker and heat to 45℃. Under mechanical stirring (300r / min), slowly add 100mL of 1% hydrogen peroxide working solution (calculated as 1000mg / L of pure hydrogen peroxide in the etching waste liquid) in batches. Maintain the temperature at 40-50℃ and stir for 1h, during which the solution changes from blue to brown. Then raise the temperature to 50℃ and continue stirring for 10min to remove excess hydrogen peroxide. Cool to 40℃, add 10g of activated carbon (40-60 mesh, calculated as 10g / L), and mechanically stir for 1.5h to adsorb oxidation products and organic impurities. Use slow-speed filter paper for vacuum filtration to remove the activated carbon, obtaining approximately 950mL of purified copper-containing filtrate.
[0028] S2. Place the purified copper-containing filtrate in a 2L beaker, heat to 35℃, and stir rapidly (magnetic stirring 400~500r / min). First, adjust the pH of the filtrate to 1.0 with 2mol / L NaOH solution, then slowly titrate with 0.5mol / L Na2CO3 solution, controlling the titration rate to gradually increase the pH until it reaches 3.2. Maintain stirring for 30min, then let it stand for 2h to allow Fe to precipitate. 3+ Sn 4+ Impurity ions were fully precipitated as hydroxides or hydrated oxides. The precipitated impurities were removed by slow-speed filtration with filter paper, yielding approximately 920 mL of a clear, bluish-green copper-containing purified solution. ICP analysis showed that the Fe content was reduced to 1.2 ppm, achieving a removal rate of 99.6%.
[0029] S3. Keep the above copper-containing purified solution at a constant temperature of 30°C, add 20g (20g / L) of chelating cation exchange resin, and stir vigorously for 60min to adsorb and remove trace amounts of residual Zn from the solution. 2+ Fe 3+ Ca 2+ Mg 2+ Metal impurity ions were removed; the solution was filtered through a separation resin to obtain approximately 900 mL of ultra-high purity copper-containing purified solution.
[0030] S4. First, prepare 100 mL of a mixed alkaline solution of Na₂CO₃-NaHCO₃ (molar ratio 1:50, total carbonate concentration 1 mol / L, pH = 8.5-9.5), heat to 70°C, and stir vigorously. Then, heat the above copper-containing purified solution to 70°C and slowly add it dropwise to the mixed alkaline solution at a rate of 2 mL / min. Add 5 g of PEG-6000 solid (5 g / L), stir slowly for 10 min until completely dissolved, add a small amount of basic copper carbonate seed crystals, stir for 10 min to disperse evenly, and control the pH of the reaction endpoint to around 8.5. After the addition is complete, maintain the temperature at 70°C and stir for 1.5 h, then let it stand for 30 min to allow it to fully convert into basic copper carbonate precipitate. Filter while hot using medium-speed qualitative filter paper to obtain a blue-green basic copper carbonate wet solid. Wash three times with 60°C hot deionized water at a solid-liquid ratio of 1:30, each time first stirring vigorously for 20 min, then sonicating for 1 min, letting stand for 5 min, and then filtering while hot. The washed wet solid basic copper carbonate was placed in a forced-air drying oven and dried at 80°C for 2 hours. After 1 hour, it was taken out and ground into powder to obtain about 24.8g of high-purity basic copper carbonate powder.
[0031] S5. Place the above-mentioned basic copper carbonate powder in an alumina crucible, put it into a muffle furnace, and heat it to 550°C at a heating rate of 5°C / min. Hold the temperature for 2 hours, and after cooling to room temperature in the furnace, grind the black powder through a 200-mesh sieve to obtain approximately 14.2g of high-purity copper oxide product. The structure of the obtained copper oxide is as follows: Figure 1 As shown, the copper oxide crystals are complete and relatively uniformly distributed within the field of view, without any obvious large-area dense or blank areas.
[0032] The test results of the copper oxide product obtained in this embodiment show that the copper oxide purity is 99.7%, the chloride ion content is 0.02%, the iron ion content is 0.0012%, the zinc ion content is 0.001%, the sodium ion content is 0.003%, the calcium ion content is 0.002%, the magnesium ion content is 0.001%, and the hydrochloric acid insoluble matter is 0.015%.
[0033] Example 2 The steps in this embodiment are largely the same as those in Embodiment 1, including the following steps: S1. Take 1L of the same acidic copper chloride etching waste liquid as in Example 1, filter it using a precision filter bag to remove suspended particles, heat it to 40°C, and slowly add 50mL of 1% hydrogen peroxide working solution (equivalent to 500mg / L of pure hydrogen peroxide in the etching waste liquid) in batches under stirring. Maintain the temperature at 40-50°C and stir for 0.5h. Then raise the temperature to 55°C and continue stirring for 15min to remove excess hydrogen peroxide. Cool to 35°C, add 5g of activated carbon (40-60 mesh, equivalent to 5g / L), stir mechanically for 1h, and then filter using slow-speed filter paper to remove the activated carbon, obtaining approximately 960mL of purified copper-containing filtrate.
[0034] S2. Heat the purified copper-containing filtrate to 30°C and stir rapidly. First, adjust the pH of the filtrate to 1.0 with 2 mol / L NaOH solution, then slowly titrate with 0.5 mol / L Na2CO3 solution to adjust the pH to 3.5. Maintain stirring for 40 min, then let it stand for 1.5 h. Filter with slow-speed filter paper to remove precipitated impurities, obtaining approximately 930 mL of clear, bluish-green purified copper-containing solution.
[0035] S3. The copper-containing purified solution is kept at a constant temperature of 25°C, 5g of chelating cation exchange resin is added, and the mixture is stirred vigorously for 15min to adsorb and remove trace metal impurity ions remaining in the solution; the resin is separated by filtration to obtain an ultra-high purity copper-containing purified solution.
[0036] S4. First, prepare a mixed alkaline solution of Na₂CO₃ and NaHCO₃ (molar ratio 1:30, total carbonate concentration 2.4 mol / L, pH=10.5). Then, heat the above copper-containing purified solution to 65℃ and slowly add it dropwise to the mixed alkaline solution at a rate of 1 mL / min. Add 0.05 g of PEG-6000 solid and control the pH at the reaction endpoint to 8.0. After the addition is complete, maintain the temperature at 65℃ and stir for 2 hours, then let it stand for 45 minutes to allow for complete conversion. Filter the solution while hot using medium-speed qualitative filter paper to obtain wet solid basic copper carbonate. Wash the solution three times with hot deionized water at 50℃ at a solid-liquid ratio of 1:30, each time with vigorous mechanical stirring for 20 minutes, sonication for 1 minute, and standing for 5 minutes, followed by hot filtration. Dry the washed basic copper carbonate at 85℃ with forced air for 3 hours to obtain high-purity basic copper carbonate powder.
[0037] S5. Place the above-mentioned basic copper carbonate powder in a muffle furnace, raise the temperature to 400°C at a heating rate of 5°C / min, hold for calcination for 3 hours, and cool to room temperature with the furnace. Then grind the black powder through a 200-mesh sieve to obtain a high-purity copper oxide product.
[0038] The test results of the copper oxide product obtained in this embodiment show that the copper oxide purity is 99.1%, the chloride ion content is 0.06%, the iron ion content is 0.0020%, the zinc ion content is 0.004%, the sodium ion content is 0.007%, the calcium ion content is 0.004%, the magnesium ion content is 0.003%, and the hydrochloric acid insoluble matter is 0.028%.
[0039] Example 3 The steps in this embodiment are largely the same as those in Embodiment 1, including the following steps: S1. Take 1L of the same acidic copper chloride etching waste liquid as in Example 1, filter it using a precision filter bag to remove suspended particles, heat it to 40°C, and slowly add 200mL of 1% hydrogen peroxide working solution (calculated as 2000mg / L of pure hydrogen peroxide etching waste liquid) in batches under stirring. Maintain the temperature at 45-50°C and stir for 1.5h. Then raise the temperature to 60°C and continue stirring for 20min to remove excess hydrogen peroxide. Cool to 45°C, add 12g of activated carbon, stir mechanically for 2h, and then filter using slow-speed filter paper to remove the activated carbon, obtaining approximately 940mL of purified copper-containing filtrate.
[0040] S2. Heat the purified copper-containing filtrate to 30°C and stir rapidly. First, adjust the pH of the filtrate to 1.0 with 2 mol / L NaOH solution, then slowly titrate with 0.5 mol / L Na2CO3 solution to adjust the pH to 3.8. Maintain stirring for 60 min, let stand for 3 h, and filter with slow-speed filter paper to remove precipitated impurities, obtaining approximately 910 mL of purified copper-containing solution.
[0041] S3. The copper-containing purified solution is kept at a constant temperature of 35°C, 20g of chelating cation exchange resin is added, and the mixture is stirred vigorously for 60min to adsorb and remove trace metal impurity ions remaining in the solution; the resin is filtered to separate the solution and obtain an ultra-high purity copper-containing purified solution.
[0042] S4. Heat the above copper-containing purified solution to 80℃, add 3g of PEG-4000 solid, and stir slowly for 10min until completely dissolved. Add a small amount of basic copper carbonate seed crystals (approximately 3% of the sample solid mass) and stir for 10min. Under 80℃ conditions, slowly add saturated Na2CO3 solution at a rate of 3mL / min, controlling the pH of the reaction endpoint to 9.0. After the addition is complete, maintain stirring at 80℃ for 1h, and let stand for 60min to allow for complete conversion. Filter while hot using medium-speed qualitative filter paper to obtain wet basic copper carbonate solid. Wash three times with 80℃ hot deionized water at a solid-liquid ratio of 1:10, each time with vigorous mechanical stirring for 20min, sonication for 1min, and standing for 5min, followed by hot filtration. Dry the washed basic copper carbonate at 90℃ with forced air for 4h, grinding once every 1h in between, to obtain high-purity basic copper carbonate powder.
[0043] S5. Place the above-mentioned basic copper carbonate powder in a muffle furnace, raise the temperature to 700°C at a heating rate of 5°C / min, hold for calcination for 1 hour, and cool to room temperature with the furnace. Then grind the black powder through a 200-mesh sieve to obtain a high-purity copper oxide product.
[0044] The test results of the copper oxide product obtained in this embodiment show that the copper oxide purity is 99.3%, the chloride ion content is 0.04%, the iron ion content is 0.0015%, the zinc ion content is 0.003%, the sodium ion content is 0.005%, the calcium ion content is 0.003%, the magnesium ion content is 0.004%, and the hydrochloric acid insoluble matter is 0.022%.
[0045] Example 4 The steps in this embodiment are basically the same as those in Embodiment 1, with the only difference being: In step S4, the amount of PEG-4000 added is 2000ppm (i.e., 2g / L), and the washing conditions are 60℃ hot deionized water and washing three times at a solid-liquid ratio of 1:50.
[0046] The obtained copper oxide product was tested and found to have a purity of 99.5%, a chloride ion content of 0.03%, and an iron ion content of 0.0013%.
[0047] Example 5 The steps in this embodiment are basically the same as those in Embodiment 1, with the only difference being: In step S2, the titration endpoint of the 0.5 mol / L Na2CO3 solution was 4.0; in step S4, the positive addition method was used, the precipitant was a single Na2CO3 solution (2 mol / L), the reaction temperature was 80℃, and the amount of PEG added was 1 g / L; in step S5, the calcination temperature was 600℃ and the temperature was maintained for 2 h.
[0048] The obtained copper oxide product was tested and found to have a purity of 99.2%, a chloride ion content of 0.05%, and an iron ion content of 0.0018%.
[0049] Comparative Example 1 The steps in this comparative example are basically the same as those in Example 1, with the only difference being: The peroxide oxidation and activated carbon adsorption steps in step S1 are omitted. The acidic etching waste liquid is directly filtered and then subjected to pH adjustment and impurity removal in step 2.
[0050] The obtained copper oxide product was tested and found to have a purity of only 96.5%, a chloride ion content of 0.20%, an iron ion content of 135 ppm, and a grayish-black color, with a significantly high impurity content.
[0051] Comparative Example 2 The steps in this comparative example are basically the same as those in Example 1, with the only difference being: In step S4, without adding PEG-4000 and seed crystals, the Na2CO3 solution is directly added dropwise to the copper-containing purification solution to carry out the precipitation reaction.
[0052] The obtained copper oxide product was tested and found to have a purity of 99.0% and a chloride ion content of 0.06%, but the particles were severely agglomerated and had an irregular morphology.
[0053] Comparative Example 3 The steps in this comparative example are basically the same as those in Example 1, with the only difference being: In step S2, the pH of the purified filtrate is directly adjusted to 8.5 using 2 mol / L NaOH solution for precipitation, without going through the selective pH removal step of 3.2-4.0.
[0054] The obtained copper oxide product, upon testing, had a purity of only 97%, a chloride ion content of 0.16%, an iron ion content of 105 ppm, and Fe content in the product was also found to be low. 3+ Sn 4+ The content of impurities is significantly higher than normal.
[0055] Then, the copper oxide products obtained in Examples 1-5 and Comparative Examples 1-3 were compared, and the results are as follows: Figure 2 As shown, the copper oxide products obtained by the embodiments of the present invention all have a purity of ≥99.1%, with Example 1 achieving the best purity of 99.7%, and the chloride ion content is ≤0.06%, which is significantly better than other products. Furthermore, the Fe impurity content in the copper oxide products obtained by Examples 1-5 is ≤20ppm, further demonstrating that the tandem purification process of "oxidation for impurity removal - selective pH precipitation - ion exchange for deep purification - reverse addition of mixed alkali solution for dechlorination - calcination purification" adopted in this invention has a significant effect on impurity removal.
[0056] Furthermore, compared to Example 1, Comparative Example 1, due to the omission of oxidation and activated carbon pretreatment steps, resulted in a significant decrease in product purity to 96.5%, with an Fe content as high as 135 ppm; Comparative Example 2, although achieving a purity of 99.0%, suffered from severe particle agglomeration and a wide particle size distribution due to the absence of PEG and seed crystals, affecting the product's performance in high-end applications; Comparative Example 3, due to the lack of selective pH purification and direct precipitation, exhibited significantly higher levels of impurities such as Fe and Sn, with a purity of only 97.0%. Therefore, the present invention employs oxidation purification, selective pH precipitation, the introduction of PEG as a morphology regulator and dispersant, and the addition of seed crystals to induce directional crystallization. Through the synergistic effect of these steps, the product achieves extremely high purity while maintaining uniform particle size and controllable morphology, meeting the demands of high-end applications.
[0057] In summary, this invention provides a method for preparing high-purity copper oxide using acidic etching waste liquid. This method employs a series of purification processes: oxidation adsorption for impurity removal, selective pH precipitation, ion exchange for deep purification, reverse addition of buffer alkali for dechlorination, and high-temperature calcination for purification. Hydrogen peroxide is used for pre-oxidation to remove Fe... 2+ Converted to Fe 3+ In conjunction with activated carbon adsorption to remove organic impurities, and then through precise pH control, Fe... 3+ Sn 4+ Impurities are selectively precipitated, and residual trace metal ions are deeply adsorbed by ion exchange resin. This triple protection significantly improves the purity of the copper purification solution. Finally, the chloride ion content is greatly reduced by adding mixed alkali solution. After calcination, the purity of the final copper oxide product can reach over 98.2%, effectively solving the technical problem of high impurity content in existing chemical precipitation products.
[0058] This invention introduces PEG as a morphology regulator and dispersant during the precipitation and crystallization process of basic copper carbonate. Simultaneously, seed crystals are added to induce directional crystallization, effectively controlling the grain size and morphological uniformity of the precipitated product. This avoids the problems of severe agglomeration and wide particle size distribution found in traditional precipitation methods. The addition of PEG reduces the surface tension of the solution and improves the solid-liquid interface properties. The resulting basic copper carbonate precursor exhibits good dispersibility, and after calcination, the copper oxide particles are uniform in size and have controllable morphology, meeting the requirements of high-end applications.
[0059] The method of this invention is simple in process and requires low equipment investment. It does not require organic extractants or expensive membrane materials, and the main reagents are inexpensive and readily available. Meanwhile, the precipitate mother liquor (mainly composed of dilute NaCl solution) can be discharged in compliance with standards or reused in etching solution preparation after simple neutralization treatment, achieving high-value recovery of copper resources and effective removal of harmful components from the waste liquid. The calcination tail gas is CO2 and water vapor, with no secondary pollution, resulting in good environmental and economic benefits.
[0060] The high-purity copper oxide product obtained by this invention has a purity of ≥98.2%, a chloride ion content of ≤0.05%, and uniform particle size. It meets the quality requirements for high-purity copper oxide in fields such as lithium-ion battery anode coatings, electronic ceramics, catalyst supports, high-precision polishing solutions, and electroplating copper oxide powder raw materials, thus broadening the application scope of the resource recovery products from acidic etching waste liquid. Furthermore, this invention allows the obtained copper oxide to be used as an anode raw material to formulate high-purity electroplating solutions according to subsequent electroplating application needs, achieving a complete resource recycling chain from waste liquid recovery to end-use applications.
[0061] The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A method for preparing high-purity copper oxide using acidic etching waste liquid, characterized in that, Includes the following steps: S1. After filtering the acidic etching waste liquid to remove suspended particles, heat it to 40-50℃ and stir to add hydrogen peroxide working solution; then raise the temperature to 50-60℃ and continue stirring to remove excess hydrogen peroxide; after cooling, add activated carbon and stir; filter to obtain purified copper-containing filtrate. S2. Heat and stir the purified copper-containing filtrate and adjust the pH, let it stand, filter to remove impurities, and obtain a copper-containing refined solution; S3. Add ion exchange resin to the copper-containing refined solution, stir, and filter to obtain a copper-containing purified solution; S4. Heat the copper-containing purification solution to 60-80℃, stir and add PEG, dissolve and then add basic copper carbonate seed crystals, stir, then dropwise transfer to sodium carbonate-sodium bicarbonate mixture, continue stirring, let stand, filter, wash and dry to obtain basic copper carbonate powder. S5. The basic copper carbonate powder is calcined, cooled, and then ground to obtain high-purity copper oxide powder.
2. The preparation method according to claim 1, characterized in that, In step S1, the hydrogen peroxide working solution has a mass fraction of 1% and is added slowly in batches at a stirring rate of not less than 300 r / min.
3. The preparation method according to claim 1, characterized in that, In step S2, the pH adjustment step includes first adjusting the pH of the filtrate to 1.0 with sodium hydroxide solution, and then slowly titrating with sodium carbonate solution to adjust the pH to 3.2-4.0, preferably 3.
5.
4. The preparation method according to claim 1, characterized in that, In step S3, the ion exchange resin is a chelating cation exchange resin, and the addition amount is 10 g / L.
5. The preparation method according to claim 1, characterized in that, In step S4, the PEG is PEG-4000, and the addition amount is 2000ppm.
6. The preparation method according to claim 5, characterized in that, The amount of basic copper carbonate seed crystals added is 1%-3% of the expected mass of the precipitate.
7. The preparation method according to claim 6, characterized in that, The molar ratio of sodium carbonate to sodium bicarbonate is 1:30-50.
8. The preparation method according to claim 1, characterized in that, In step S5, the calcination conditions are calcination at 500°C for 2 hours.